Fiber optic: lab companion - Harum, Norharyati; Md. Shah, Wahidah; Ramly, Marliza (Penerbit UTeM Press, 2023)
Fiber optic module includes fiber optic cables, connectors, adapters, and testing equipment. It is a teaching tool for students to learn and practice the skills needed to work with fiber optic networks. students can use the fiber optic module to practice splicing and terminating cables. The fiber optic kit includes the Fiber Optic: Lab Companion module.